Analisis Kualitas Produk dan Pelayanan di Imadji Coffee Kota Denpasar - Dwijaksara, Denada Homia Bestari; Hartiati, Amna; Sadyasmara, Cokorda Anom Bayu (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2023)
Imadji Coffee is a culinary business that focuses on processed coffee drinks, but there are still problems, namely a decrease in sales. This research was conducted to determine the level of customer satisfaction with product and service quality, determine marketing strategies through delivery applications, determine the performance and level of customer satisfaction as well as determine the attributes and service systems used at Imadji Coffee Denpasar City. The method used in calculating the level of customer satisfaction, namely Important Performance Analysis (IPA). Determination of the sample using Slovin calculations with a total number of respondents as many as 88 people. The results of the study indicate that the strategy used by Imadji Coffee Denpasar City in an effort to market products in the delivery application is by utilizing the application Grab Food and Go-food which until now has become an application with a high number of users. Application Grab Food being the dominant platform used with a value of 69%, meanwhile Go-food with its user platform 31%. Attributes that are considered most important by consumers are the suitability of prices and products with a score of 408 and the service system that is considered the most important by consumers is the speed of service with a score of 396. Promo offers are performance with the highest level of performance, namely at a score of 334 and so is consumer satisfaction with the highest satisfaction level is 90%. The results obtained on the attribute that most needs to be updated are location convenience.